Fenestrated azygos A2 segment: a rare anatomic variation. Issue 1 (December 2015) - Rahmanian, Abdolkarim; Derakhshan, Nima
Abstract Advancement in neurovascular imaging has led to detection of abnormalities and normal anatomic variations. Most of anatomical variations in cerebral vasculature are asymptomatic and found incidentally; however, some may increase the risk of aneurysm formation and subsequent subarachnoid or intracranial hemorrhage. Here in, we report fenestration within an azygos A2 segment, as an incidental finding, which is an extremely rare anatomic variation in a patient suffering subarachnoid hemorrhage (SAH). However, there was no correlation found between SAH and the mentioned anatomic variation. To author's knowledge this is the first report of such anatomic variation with providing source images of brain CT angiograms.